Материалы по питанию мухоловок (Passeriformes, Muscicapidae) юга Советского Дальнего Востока - Смогоржевский, Л.А.; Пекло, А.М. (Вестник зоологии, 1980)
The article deals with the data on nutrition for 8 species of Muscicapidae: Terpsi-phone paradisi incei, Ficedula zanthopygia, F. mugimaki, F. parva albicilla, Cyanoptila cyanomelana, Muscicapa sibirica, M. griseisticta, M. latirostris from the South of the Soviet Far East. The materials are based on the analysis of 209 food assays. The eating behaviour of certain species is described.